Logical Connectors’ Use and Writing Quality in EFL Learners and Native Speakers’ Essay Writing - Malki, Fatima Zohra (Journal of Human Sciences, 2016)
The study presents an investigation of the writing performance of Algerian third year EFL students at the Department of Letters and the English Language at the University of Constantineto diagnose the issues concerning the appropriate use of cohesive devices.By extension, it is also intended to explore how learners use the logical connectors and the effect of suchcohesivedeviceson their writing quality. For this, we hypothesised that if students have higher writing proficiency, they will use accurately logical connectors, and will better use them semantically and stylistically.The analysis of the findings providedus with a clear picture that there is no correlation between the learners’ use of logical connectors and their writing quality. Hence, there is no clear pattern of using connectors in relation to the level of students’ writing performance.